Selenomethionine as a dietary supplement for laying hens: Impacts on lipid peroxidation and antioxidant capacity in fresh and stored eggs - dos Reis J.H.* (2019)
© 2019 Wiley Periodicals, Inc.The objective of this study was to determine whether supplementing the diets of laying hens with selenomethionine (SM, 1% selenium) improves performance and egg quality. We supplemented diets with SM as follows: T0 control (without SM); T5, T10, T15, and T20 were supplemented with 5, 10, 15, and 20 mg of SM/kg of feed, respectively (equal to 0.05, 0.10, 0.15, and 0.20 mg selenium/kg of feed). T5 and T10 hens showed better feed conversion per kg of egg, percentage of laying, higher daily feed intake, and higher average egg weight. The eggs of hens supplemented with SM had lower levels of lipoperoxidation (LPO) in fresh (T15 and T20) and stored eggs (T20). Glutathione peroxidase (GPx) and superoxide dismutase (SOD) activities, as well as total antioxidant capacity were greater in egg yolks after storage (T10; T15; T20 compared to T0). Hens supplemented with SM had elevated GPx and SOD activities and decreased oxidative reactions. Practical applications: Selenium has several nutraceutical properties, with beneficial effects on the health of the animal and the food produced from them (eggs, in this case). Selenomethionine supplementation in the diet of laying hens improves productive efficiency, stimulates the antioxidant system and reduces lipid peroxidation in the egg yolk. Egg-laying hens that received selenomethionine showed minimized lipid peroxidation in stored eggs, possibly improving shelf life of the eggs.